PENGABDIAN KEPADA MASYARAKAT: PELATIHAN KOMUNIKASI LISAN BAHASA INGGRIS BAGI SISWA/I SMA - Halim, Suwarni Wijaya (Universitas Bunda Mulia, 2025)
In today's globalized world, English language proficiency has become an important asset for personal and professional success. Among the various skills related to learning English, English listening and speaking skills are very important. To hone English listening and speaking skills, the English Language study program of Bunda Mulia University conducted community service at SMA Fons Vitae 1, East Jakarta. This community service was conducted face-to-face from September 12 to November 14, 2024 from 2.45 PM to 4.15 PM, and the activity was carried out in 7 sessions. Participants in this community service were thirty students of grade X and XI of SMA Fons Vitae 1, and the speakers were lecturers from the English Language study program of Bunda Mulia University. A series of topics related to English listening and speaking skills were taught by the speakers, including recounting stories, describing products, participating in meetings, and persuasive speaking. First, the speakers gave ice-breaking sessions, which were then followed with the presentation of materials and references according to the topic and practice sessions by the students. In the last session, an evaluation was conducted to assess the English speaking skills of the students. Most of the students were quite proficient in speaking English and were able to explain their opinions very well. However, there were some students who experienced difficulties. From the results of the feedback questionnaire, it can be concluded that this community service had a positive impact on the students of SMA Fons Vitae 1. The students of SMA Fons Vitae 1 considered that the training was educational, objective, accountable, and transparent.